Connecting biology with psychology to make sense of appetite control. Issue 4 (December 2016) - Rogers, P. J.; Ferriday, D.; Jebb, S. A.; Brunstrom, J. M.
Abstract: Eating more than is required to maintain bodyweight is weakly resisted physiologically, as appetite does not closely track body energy balance. What does limit energy intake is the capacity of the gut to accommodate and process what is eaten. As the gut empties, we are ready to eat again. We typically refer to this absence of fullness as 'hunger', but in this state, even when it is prolonged ( e.g . by missing one or two meals), our mental and physical performance is not compromised because body energy stores are mobilised to sustain energy supply to our brain and muscles. We illustrate this by discussing research on the effects of missing breakfast. Contrary to conventional wisdom, it appears that missing breakfast leads to a reduction in total daily energy intake and does not impair cognitive function (in adequately nourished individuals). The problem with missing a meal or eating smaller meals, however, is that we miss out on (some of) the pleasure of eating (food reward). In current studies, we are investigating how to offset the reduced reward value of smaller food portions, by, for example, altering flavour intensity, food variety and unit size, in order to maintain overall meal satisfaction and thereby reduce or eliminate subsequent compensatory eating.